2019
DOI: 10.1155/2019/9757369
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Knee Osteoarthritis on Hip and Ankle Gait Mechanics

Abstract: Introduction. Knee osteoarthritis (OA) can affect the hip and ankle joints, as these three joints operate as a kinetic/kinematic chain while walking. Purpose. This study was performed to compare (1) hip and ankle joint gait mechanics between knee OA and control groups and (2) to investigate the effects of knee gait mechanics on the ipsilateral hip and ankle joint. Methods. The study group included 89 patients with end-stage knee OA and 42 age- and sex-matched controls without knee pain or OA. Kinetic and kinem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 23 publications
2
46
0
Order By: Relevance
“…Similarly, Segal et al 35 reported joint power differences between symptomatic KOA patients and high-functioning controls. In one of our previous studies, we have reported that difference between maximum and minimum value of both hip flexion angle and hip adduction angle were smaller in KOA patients compared with control group 36 . Weidow et al have reported that 37 the maximum value of hip rotation moment significantly differed between symptomatic and asymptomatic group.…”
Section: Discussionmentioning
confidence: 63%
“…Similarly, Segal et al 35 reported joint power differences between symptomatic KOA patients and high-functioning controls. In one of our previous studies, we have reported that difference between maximum and minimum value of both hip flexion angle and hip adduction angle were smaller in KOA patients compared with control group 36 . Weidow et al have reported that 37 the maximum value of hip rotation moment significantly differed between symptomatic and asymptomatic group.…”
Section: Discussionmentioning
confidence: 63%
“…The ankle and foot play an important role in biomechanical alterations in the lower limbs of individuals with KOA. As the axis of movement in the lower extremity, the ankle is biomechanically related to problems in the knee [4]. An increased knee adduction angle is observed in subjects with early knee osteoarthritis [5], and a lateral shift in foot center of pressure (COP) could reduce the knee adduction moment through shortening the knee lever arm [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, hip RoM did not significantly differ among groups in this study, which may be due to the criteria used to divide patients into groups. In previous studies in which reduced hip RoM was observed in severe KOA, patients with severe KOA were defined as those who had a KL grade 4 change in knee radiography or who were indicated for joint replacement surgery 5 , 9 . In this study, advanced KOA was defined as a KL grade 3 or 4 in knee radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in knee joint angles during the gait cycle between patients with KOA and healthy adults have been reported. Previous studies showed that gait kinematics of the hip joints could be affected by KOA 5 , 9 . Furthermore, gait variability, which a factor associated with falls 10 , 11 , could be affected by KOA 12 14 .…”
Section: Introductionmentioning
confidence: 99%